Statistical Modeling for Prediction of CCT Diagrams of Steels Involving Interaction of Alloying Elements - MARTIN, HENRY; AMOAKO-YIRENKYI, PETER; POHJONEN, AARNE; FREMPONG, NANA K.; KOMI, JUKKA; SOMANI, MAHESH (Springer Nature, 2024)
This article is published by Springer Nature 2020 and is also available at https://doi.org/10.1007/s11663-020-01991-w